Volume 2B: Turbomachinery 2016
DOI: 10.1115/gt2016-56044
|View full text |Cite
|
Sign up to set email alerts
|

Flat-Plate Boundary Layers in Accelerated Flow

Abstract: Flow in turbomachines is generally highly turbulent. The boundary layers, however, often exhibit laminar-to-turbulent transition. But also relaminarization of the turbulent flow may occur. The state of the boundary layer is important, since it strongly influences transport phenomena like skin friction and heat transfer. It is therefore vitally important for the designer to understand the process of boundary layer transition and to determine the position of transition onset and the length of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…This then results in the formation of fewer vortices which are stronger due to acceleration-induced stretching. Consequently, this led to uncharacteristically more violent events, which correlates with the findings from the previous studies (McEligot & Eckelmann 2006;Bader et al 2016).…”
Section: Studies Of Spatial Accelerationsupporting
confidence: 89%
“…This then results in the formation of fewer vortices which are stronger due to acceleration-induced stretching. Consequently, this led to uncharacteristically more violent events, which correlates with the findings from the previous studies (McEligot & Eckelmann 2006;Bader et al 2016).…”
Section: Studies Of Spatial Accelerationsupporting
confidence: 89%
“…To sum up, the wall shear stress and the velocity profiles have shown that the model is able to predict relaminarization. The behavior during relaminarization and retransition computed by the γ-Re θ transition model agrees qualitatively well with published measurements [Bader et al, 2016a] and DNS data ].…”
Section: Numerical Setupsupporting
confidence: 88%
“…Therefore, at the Institute for Thermal Turbomachinery and Machine Dynamics (ITTM) of Graz University of Technology a project was launched in order to understand the process of relaminarization and its phases even further and test common threshold values for relaminarization by acceleration. First measurements performed at the institute already showed good results and relaminarization was detected [Bader et al, 2016a].…”
Section: Introductionmentioning
confidence: 98%